PENGARUH MOTIVASI, PENGALAMAN, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT. NOR COFFEE INDONESIA - Juwita, Nurma Intan; Setianingsih, Wahyu Eko; Rusdiyanto, Rusdiyanto (Fakultas Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of motivation, experience, and work discipline on employee performance at PT Nor Coffee Indonesia. The type of research used is quantitative research and data collection techniques using observation, interviews and questionnaires to 50 respondents with census techniques. The analytical tools used in this research are validity test, reliability test, classical assumption test, multiple linear regression analysis, T test, and R2 test. The results of testing the first hypothesis (H1) show that the motivation variable is 0.173 which is greater than 0.05, which means that the motivation variable has no effect on employee performance. The results of testing the first hypothesis (H2) show that the experience variable is 0.610 where the value is greater than 0.05, it can be concluded that the experience variable has no effect on employee performance. The results of testing the first hypothesis (H3) show that the work discipline variable is 0.00 where the value is smaller than 0.05, it can be concluded that the work discipline variable has a variable on employee performance